Patients with Nonalcoholic Fatty Liver Disease Have a Low Response Rate to Vitamin D Supplementation. Issue 10 (16th August 2017) - Dasarathy, Jaividhya; Varghese, Rony; Feldman, Abram; Khiyami, Amer; McCullough, Arthur J; Dasarathy, Srinivasan
Abstract: Background: Hypovitaminosis D is associated with an increased severity of nonalcoholic fatty liver disease (NAFLD), but reports on the response to cholecalciferol (vitamin D3 ) supplementation are conflicting. Objective: The objective of this study was to determine if standard vitamin D3 supplementation is effective in NAFLD with hypovitaminosis D. Methods: Sixty-five well-characterized adults [age (mean ± SD): 51.6 ± 12.3 y] with biopsy-proven NAFLD were screened. Forty-two patients (the ratio of men to women was 13:29) had hypovitaminosis D (plasma 25-hydroxyvitamin D [25(OH)D] <30 ng/mL). An observational study was performed in NAFLD patients with hypovitaminosis D treated with 2000 IU cholecalciferol (vitamin D3 ) daily for 6 mo per clinical practice. Plasma 25(OH)D, hepatic and metabolic panels, and metabolic syndrome components were assessed before and after cholecalciferol supplementation. Body composition was measured by using bioelectrical impedance analysis. The primary outcome measure was plasma 25(OH)D ≥30 ng/mL at the end of the study. Secondary outcomes included change in serum transaminases, fasting plasma glucose, and insulin and homeostasis model assessment of insulin resistance (HOMA-IR). Chi-square, Student's t tests, correlation coefficient, and multivariate analysis were performed. Results: Twenty-six (61.9%) patients had nonalcoholic steatohepatitis (NASH), and 16 (38.1%) had hepatic steatosis. After 6 mo of cholecalciferol supplementation, plasma 25(OH)D ≥30 ng/mL was observed in 16 subjects (38.1%; responders) whereas the remaining 26 patients (61.9%) were nonresponders with plasma 25(OH)D <30 ng/mL. Significantly fewer ( P < 0.01) patients with NASH were responders (4 of 26, 15.4%) than those with hepatic steatosis (12 of 16, 75%). Baseline fasting serum alanine aminotransferase, plasma glucose, and HOMA-IR were similar in the responders and nonresponders, but the NASH score on the liver biopsy was lower (16.5%) in the responders ( P < 0.001). Nonresponders had a higher fat mass (10.5%) and lower fat-free mass (10.4%) than responders did. End-of-treatment alanine aminotransferase and HOMA-IR improved only in responders. The baseline HOMA-IR and histological NASH score were independent predictors of nonresponse to cholecalciferol supplementation. Conclusions: Daily supplementation with 2000 IU cholecalciferol for 6 mo did not correct hypovitaminosis D in the majority of patients with NASH. Further studies are needed to determine if higher doses are effective. This trial was registered at clinicaltrials.gov as 13–00153.